Remarks at the United Nations Biodiversity Conference : Aligning Finance and Building Capacity for an Ecological Civilization - Malpass, David (World Bank, Washington, DC, 2021)
World Bank Group President David Malpass discussed biodiversity and climate change being closely interlinked, with terrestrial and marine ecosystems serving as critically important carbon sinks. At the same time climate change acts as a direct driver of biodiversity and ecosystem services loss. The World Bank has financed biodiversity conservation around the world, including over 116 million hectares of Marine and Coastal Protected Areas, 10 million hectares of Terrestrial Protected Areas, and over 300 protected habitats, biological buffer zones and reserves. The COVID pandemic, biodiversity loss, climate change are all reminders of how connected we are. The recovery from this pandemic is an opportunity to put in place more effective policies, institutions, and resources to address biodiversity loss.